Computer Control of Drug Delivery by Continuous Intravenous Infusion: Bridging the Gap between Intended and Actual Drug Delivery. (March 2015) - Parker, Michael J.; Lovich, Mark A.; Tsao, Amy C.; Wei, Abraham E.; Wakim, Matthew G.; Maslov, Mikhail Y.; Tsukada, Hisashi; Peterfreund, Robert A.
Abstract : Background: Intravenous drug infusion driven by syringe pumps may lead to substantial temporal lags in achieving steady-state delivery at target levels when using very low flow rates ("microinfusion"). This study evaluated computer algorithms for reducing temporal lags via coordinated control of drug and carrier flows. Methods: Novel computer control algorithms were developed based on mathematical models of fluid flow. Algorithm 1 controlled initiation of drug infusion and algorithm 2 controlled changes to ongoing steady-state infusions. These algorithms were tested in vitro and in vivo using typical high and low dead volume infusion system architectures. One syringe pump infused a carrier fluid and a second infused drug. Drug and carrier flowed together via a manifold through standard central venous catheters. Samples were collected in vitro for quantitative delivery analysis. Parameters including left ventricular max dP/dt were recorded in vivo . Results: Regulation by algorithm 1 reduced delivery delay in vitro during infusion initiation by 69% (low dead volume) and 78% (high dead volume). Algorithmic control in vivo measuring % change in max dP/dt showed similar results (55% for low dead volume and 64% for high dead volume). Algorithm 2 yielded greater precision in matching the magnitude and timing of intended changes in vivo and in vitro . Conclusions: Compared with conventional methods, algorithm-based computer control of carrier and drug flows can improve drug delivery by pump-driven intravenous infusion to better match intent. For norepinephrine infusions, the amount of drug reaching the bloodstream per time appears to be a dominant factor in the hemodynamic response to infusion. Abstract : Computer-executed algorithms can coordinate the output of pumps infusing drug and carrier fluid to reduce delivery lag time in vitro and in vivo.